Possible sertraline-induced extrapyramidal adverse effects in an adolescent - Wang L; Huang J; Shan S; Ding J; Lai J; Xu Y; Hu S (Neuropsychiatric Disease and Treatment, 2016)
Lian-fang Wang,1 Jin-wen Huang,1 Si-yang Shan,2 Jia-hong Ding,3 Jian-bo Lai,1,2 Yi Xu,1,4 Shao-hua Hu1,4 1Department of Psychiatry, The First Affiliated Hospital, Zhejiang University School of Medicine, 2Faculty of Clinical Medicine, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Psychology, University of Hong Kong, Pokfulam, Hong Kong; 4The Key Laboratory of Mental Disorder’s Management in Zhejiang Province, National Clinical Research Center for Mental Health Disorders, Hangzhou, Zhejiang, People’s Republic of China Abstract: Sertraline has been considered to be a relatively safe selective serotonin reuptake inhibitor for adolescents for a long time. We report herein a case of a 16-year-old Chinese boy with depression who experienced extrapyramidal-like effects, for example, facial spasm, upper limb dystonia, akathisia, and other disturbed behaviors, while being treated with sertraline 200 mg per day. His movement symptoms were significantly alleviated after the discontinuation of sertraline and the administration of scopolamine. This finding indicates that albeit infrequent, sertraline may cause severe extrapyramidal symptoms in adolescent patients, suggesting that clinicians should be alert to the neurological side effects of sertraline in young patients. Keywords: adolescents, selective serotonin reuptake inhibitors, sertraline, extrapyramidal symptoms